2016
DOI: 10.18052/www.scipress.com/ilns.52.19
|View full text |Cite
|
Sign up to set email alerts
|

<i> In Vitro</i> Control of Tomato (<i>Solanum lycopersicon</i> L.) Fruit Rot Caused by Fungi Using Two Plant Extracts

Abstract: Abstract. The inhibitory properties of the ethanolic and methanolic leaf extracts of Vernonia amygdalina and Cola acuminata on the fungal pathogens isolated from infected tomato fruits were investigated. The pathogens were Fusarium moniliformes and Rhizopus stolonifer. Various concentrations of the extracts ranging from 10,20,30, 40, 50, 60, 70, 80, 90 and 100% were separately added to PDA media. The fungal pathogens were separately inoculated into the media and incubated for seven days. Antifungal effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…To date, most researchers have focused on V. amygdalina crude extract in order to uncover its potential as an antifungal agent for the management of plant disease. Recent findings found that V. amygdalina ethanol extracts showed a good ability to inhibit postharvest fungal pathogens Rhizopus stolonifer and Fusarium moniliforme [ 16 , 17 ]. In another study, in an in vitro test using an ethanol crude extract of V. amygdalina at 300 mg/mL, the growth of Cercosporella persica and Curvularia lunatus were completely inhibited [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most researchers have focused on V. amygdalina crude extract in order to uncover its potential as an antifungal agent for the management of plant disease. Recent findings found that V. amygdalina ethanol extracts showed a good ability to inhibit postharvest fungal pathogens Rhizopus stolonifer and Fusarium moniliforme [ 16 , 17 ]. In another study, in an in vitro test using an ethanol crude extract of V. amygdalina at 300 mg/mL, the growth of Cercosporella persica and Curvularia lunatus were completely inhibited [ 18 ].…”
Section: Introductionmentioning
confidence: 99%